Potential reduction in energy consumption in consolidated built environments. An analysis based on climate, urban planning and users - Esther Compte Coloma (Vitruvio: International Journal of Architectural Technology and Sustainability)
In order to minimise the environmental problems of energy consumption this study aims to assess the potential energy demand reduction of the three main building types within three urban configurations of a Mediterranean city in the Comunitat Valenciana Region, Spain. To do so this project aims to identify the urban configuration which makes the best use of sun and natural ventilation, and whether this potentially affects the energy consumption of users in three vulnerable neighbourhoods as an analysis methodology prior to any intervention on the building stock. Factor analysis was carried out in summer taking into account the greater influence of the climate factors in the warm region under study. Therefore, winter conditions were excluded from this analysis as the installations, and the state of conservation of the envelope were the main factors affecting the energy consumption at this time of year. The results obtained show that there is true potential for reducing consumption in the buildings analysed. Due to the viability and easy implementation of these actions, and given the embodied energy, the measures for optimising the envelope of buildings are inadvisable or to be considered only as a last resort.